Clinical Spectrum of Udavartta in the Limelight of Vega and Vegarodha–A Narrative Review - Abhilash , M (International Research Journal of Ayurveda & Yoga, 2022)
Udavartta is a vatikaroga, predominantly produced by vegarodha, the incidence of which is increasing as a part of the fast and sedentary lifestyle. The primary site of udavartta is Koshta because of a multifactorial convergence of doshakopa towards the highly susceptible apanavata. Understanding the physiology of vegas help a lot to have an insight over the pathology in udavartta. Vegas, which can be categorized as either programmed or as a result of some irritation / deficit, are sophisticated functions of ‘vata system’ of the body to maintain the homeostasis. Vegarodha brings about a disturbance in this homeostasis, which is progressed to the disease udavartta. There are various conditions, which contradict as well as coincide with the pathology of udavartta. These conditions have to be either ruled out or confirmed to be present, before we diagnose or start to treat udavartta. As udavartta is a multidimensional and multifactorial disease, the management of udavartta also demands this kind of depth and variety. Vatanulomana, being the primary objective, the treatment of udavartta differs to a great extent, according to its type and severity. The treatment of udavartta is significant right from its chayavastha and is being expanded to a ‘broad spectrum udavartta therapy’ as it reaches the bhedavastha. Beyond Ayurveda, the omnipotent vata can be controlled and synchronized using pranayama and other Yogic techniques. Thus, the concepts and treatment modalities of Ayurveda; when complemented with a Yogic base and updated to the needs of modern society, can render better results.